Pelvic Organ Prolapse and Its Associated Factors Among Women Attending the Gynecology Outpatient Clinic at a Tertiary Hospital in Southwestern Uganda - Tugume R; Lugobe HM; Kato PK; Kajabwangu R; Kanyesigye H; Masembe S; Kayondo M (Dove Medical Press, 2022)
Rodgers Tugume, Henry Mark Lugobe, Paul Kalyebara Kato, Rogers Kajabwangu, Hamson Kanyesigye, Sezalio Masembe, Musa Kayondo Department of Obstetrics and Gynecology, Mbarara University of Science and Technology, Mbarara, UgandaCorrespondence: Rodgers Tugume, Department of Obstetrics and Gynaecology, Mbarara University of Science and Technology, Mbarara, Uganda, Tel + 256-771412807, Email rodgerstugume@gmail.comPurpose: To determine the prevalence, clinical stage at presentation and factors associated with pelvic organ prolapse (POP) among women attending the gynecology outpatient clinic at Mbarara Regional Referral Hospital (MRRH), Uganda.Methods: We conducted a cross-sectional study at the gynecology outpatient clinic of MRRH from September 2019 to January 2020. Women aged 18- 90 years were systematically sampled and recruited into this study. An interviewer administered questionnaire was used to collect participants' socio-demographic, obstetric, gynecological and medical factors. POP stage was obtained by using the pelvic organ prolapse-quantification system. Multivariable logistic regression analysis was done to determine factors associated with pelvic organ prolapse.Results: Of 338 participants enrolled, the prevalence of POP was 27.5% [n = 93, 95% Cl: 23.0- 32.5]. POP stages were stage I 11.8% (n = 11), stage II 63.4% (n = 59), stage III 16.1% (n = 15) and stage IV 8.9% (n = 8). Grand-multiparity (aOR 17.1, 95% CI: 1.1- 66.6), birth weight more than 3.5kg (aOR 3.7, 95% CI: 1.1- 12.6), perineal tears (aOR 6.5, 95% CI: 2.1- 20.2), peasant farmer (aOR 6.9, 95% CI: 1.6- 29.9) and duration of labour in the first delivery > 24 hours (aOR 5.7, 95% CI: 1.2- 29) were significantly associated with POP.Conclusion: POP is common among women attending the gynecology clinic at MRRH with most of them presenting with stage II. There should be routine screening for POP to enable early identification and management especially in those who are grand multiparous, peasant farmers and have a history of perineal tears.Keywords: pelvic organ prolapse, prevalence, factors associated, pelvic organ prolapse quantification system, southwestern Uganda